PHP, MySQL, JavaScript & HTML5 all-in-one for dummies - Suehring, Steve (--For dummies., 2013)
Get the basics on four key web programming tools in one great book! PHP, JavaScript, and HTML5 are essential programming languages for creating dynamic websites that work with the MySQL database. PHP and MySQL provide a robust, easy-to-learn, open-source solution for creating superb e-commerce sites and content management. JavaScript and HTML5 add support for the most current multimedia effects. This one-stop guide gives you what you need to know about all four!